Nanofiltration Treatment For Pesticides Removal : A Case Study For Atrazine And Dimethoate [SB951. T161 2007 f rb]. - Tan, Lian See (2007)

(untitled)
Tesis ini memfokuskan kepada penyingkiran racun serangga dari larutan akues menggunakan membran penurasan nano. Dua jenis racun serangga, atrazin dan dimetoat, telah dipilih untuk diuji. This thesis focuses on the removal of pesticide from aqueous solution using nanofiltration membrane. Two pesticides, atrazine and dimethoate, were selected for study in this research.